2009
DOI: 10.1038/ja.2009.117
|View full text |Cite
|
Sign up to set email alerts
|

In vitro synergistic activity of tigecycline and colistin against XDR-Acinetobacter baumannii

Abstract: The emergence of extensive drug-resistant (XDR) Acinetobacter baumannii limits the therapeutic options and leads to high mortality in intensive care units. Combined antibiotic therapy is frequently recommended for the treatment of these infections. Colistin (CO) and tigecycline (TIG), alone or in combination with other antimicrobials, are the most commonly used antibiotics in the treatment of these resistant infections. In this study, the in vitro synergistic activity of TIG and CO were tested for 25 XDR-A. ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 19 publications
3
26
1
1
Order By: Relevance
“…Combination therapy plays an important role in the management of severe A. baumannii infection. Similarly to other published studies [37][38][39][40] , the results of this in vitro trial provide evidence that tigecycline used in combination with either colistin sulfate or levofloxacin will produce clinically relevant synergy against A. baumannii , and that it might be useful to use tigecycline in combination with colistin sulfate or levofloxacin to produce a rapid enhancement of bactericidal activity, to prevent or delay the emergence of resistance, and to gain synergistic interaction against this organism. The purpose of this study was to examine whether the PAEs induced by drug combinations differed from the PAEs induced by the drugs alone.…”
Section: Discussionsupporting
confidence: 53%
“…Combination therapy plays an important role in the management of severe A. baumannii infection. Similarly to other published studies [37][38][39][40] , the results of this in vitro trial provide evidence that tigecycline used in combination with either colistin sulfate or levofloxacin will produce clinically relevant synergy against A. baumannii , and that it might be useful to use tigecycline in combination with colistin sulfate or levofloxacin to produce a rapid enhancement of bactericidal activity, to prevent or delay the emergence of resistance, and to gain synergistic interaction against this organism. The purpose of this study was to examine whether the PAEs induced by drug combinations differed from the PAEs induced by the drugs alone.…”
Section: Discussionsupporting
confidence: 53%
“…11,12 Nevertheless, several studies have shown that tigecycline-or rifampicinbased regimens are more effective for treating severe infections caused by MDR A baumannii. 13,14 To date, no studies are available on the efficacy of rifampicin or combination rifampicin/colistin against A baumannii isolates in Taiwan, although rifampicin has been used for the long-term treatment of infections caused by Mycobacterium tuberculosis. Furthermore, the spread of MDR A baumannii with resistance to tigecycline, rifampicin, and colistin in hospitals has never been reported in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced activity or bactericidal synergism occurred with TIG plus carbapenems, levofloxacin, amikacin and RIF in various in vitro studies [76][77][78]. Results of the combination of TIG with COL are controversial [79][80][81].…”
Section: Tigecycline (Tig)mentioning
confidence: 94%
“…However, it is well documented that when used alone RIF shows rapid development of resistance, thus its combination with other antimicrobials is necessary [105,106]. Although an additive effect or synergism has been observed for combinations of RIF with various agents such as carbapenems, TIG or SAM [81,105], the most promising combination is that of RIF with COL.…”
Section: Rifampicinmentioning
confidence: 97%